Teachers' efficacy beliefs among novice Malaysian teachers. - Bakar, Ab. Rahim; Mohamed, Shamsiah (Common Ground Publishing, 2009)
This article is a presentation of the findings of research conducted on the teacher’s sense of efficacy among novice teachers in Malaysia. A total of 727 novice teachers participated in the study. Novice teachers are teachers who have been in service for three years or less. Teachers’ sense of efficacy was assessed using the Ohio State Teacher Efficacy Scale (OSTES), developed by Tschannen- Moran and Woolfolk Hoy. The level of overall teaching efficacy among novice teachers was moderate (Mean: 3.87; S.D: 0.62). The findings indicated that they were moderately efficacious in terms of student engagement, instructional strategies, and classroom management. The implication of the study to teacher-education programs in Malaysia is discussed.